Zakonnica w radzieckim piekle. Czerwona katorga Julii Danzas - Kościołek, Anna (Slavia Orientalis, 2026)
This essay attempts to identify and interpret the dispersed signs of religious identity in the memoirs Red Gaols by Julia Danzas, an aristocrat, talented thinker, religious and social activist, and Catholic nun. Since they do not constitute a clearly delineated narrative thread, an operational approach to their analysis was adopted. The theoretical framework of the study is provided by the concept of religious identity developed by Father Leon Dyczewski (1936– 2016), a sociologist, theologian, and philosopher associated with the Catholic University of Lublin. Central to this approach is the assumption that religious identity does not necessarily take the form of explicit verbal declarations but may instead be manifested through everyday attitudes, moral responses, and ways of interpreting reality. The application of this framework appears particularly justified in the case of the analysed text, which lacks an overt worldview or confessional statements. The study demonstrates that religious identity in Red Gaols manifests itself indirectly through moral choices, resilience, and engagement with others, rather than through explicit declarations of faith.